Comparison of tooth size discrepancy of three main ethnics in Malaysia with Bolton's ratio - Rahman, A.N.A.A.; Othman, Siti Adibah (Penerbit Universiti Kebangsaan Malaysia, 2012)
The objective of this study was to investigate the applicability of Bolton's ratios in orthodontic population of Malaysian main ethnics; Malay, Chinese and Indians. Ninety convenient samples consisting of 30 pre-orthodontic study casts from each ethnic that fits the inclusion criteria were selected. The greatest mesiodistal widths of each tooth from six to six for overall ratio and three to three for anterior ratio were measured using a digital callipers linked to Hamilton Arch Tooth System software to the nearest 0.01mm. Means of the ratios were calculated using Bolton analysis. One sample t-test statistic analysis was carried out to compare the means with Bolton values of anterior ratio and overall ratio and one-way ANOVA was used to analyze comparison between ethnic groups of the anterior ratio and the overall ratio with the level of statistical significance set at p < 0.05. However, there were no significant differences when comparing Bolton values with Chinese and Indian anterior and overall ratios. The Bolton standards could be applied to Malaysian Chinese, Indians and Malay's female. Subsequently, a specific standard should be used for the Malays orthodontic population.